CATALYTIC COMPOSITION CONTAINING PALLADIUM AND CHROMIUM OXIDES (1976)
1424382 Exhaust gas treatment catalysts NISSAN MOTOR CO LTD 16 Jan 1973 [18 Jan 1972] 2220/73 Heading B1E [Also in Division Cl] Catalysts free from copper oxide comprise a carrier and supported thereon palladium and chromium oxides and at least one of Mg, Sr, Ba, Al, Zr, V and Bi oxides, the contents of Pd and Cr being, respectively, 0.0003-0.1 and 0.05- 3.0 g-atoms per litre of carrier and the total amount of metal(s) in the additional oxide(s) being 1/ 50 -¢ the amount (in g-atoms) of the chromium. The carrier may be monolithic or particulate, coated or uncoated. The catalysts may be made by impregnation of the carrier with compounds decomposable to the oxides and/or by mixing the carrier with hydroxides, followed by calcination.